Interlinking Socio-Economic and Environmental Factors Driving Biodiversity Loss in Vhembe Biosphere - Henry Nuwarinda; Samuel Adewale Adelabu; Abel Ramoelo; Olufemi Sunday Durowoju; Colbert Mutiso Jackson; Katlego Mashiane (Geography Notebooks)
Abstract